(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Knowledge regarding privacy and confidentiality at healthcare is mandatory for all doctors as it is deeply rooted in core part of the medical ethics. To gauge the extent of knowledge of para-clinical and clinical medical students on privacy and confidentiality in healthcare. Materials and methods: A cross sectional survey was conducted in between June 2023 to September 2023 on 300 medical students of Chattagram Maa-O-Shishu Hospital Medical College (CMOSHMC). A pretested questionnaire was used and data was analyzed by SPSS 22. Results: Out of 300 responses from medical students of phase II, phase III and phase IV MBBS, the number of students were predominantly female and religion were Islam. The age range of the participants was from 20-25 years. Conclusion: The medical students of this study had a reasonable knowledge about privacy and confidentiality in healthcare. However, the teaching of privacy and confidentiality related medical practice should be part of the medical curriculum to strengthen these attitudes so that they can maintain professional secrecy and sustain the standard of good clinical practice following medical ethics. JCMCTA 2024 ; 35 (1) : 135-138